Comparison of Serum Procalcitonin With Blood Culture (Gold Standard) For the Identification of Bacterial Infection in Critically Ill Patients - Abid, Somia; Khan, Ejaz Hassan; Shafi, Mohsin; Rafiq, Ahmed; Shaheena, Shaheena; Gul, Amna (ADVANCES IN BASIC MEDICAL SCIENCES, 2021)
Background: To evaluate the determinative correctness of Procalcitonin ( PCT ) for identification of bacterial sepsis (gram positive and gram negative bacterial infection ) in seriously morbid subjects who will get admission in ICU/emergency deptt. of Khyber teaching hospital and comparing it with blood cultures (gold standard ) . Methodology: It was a cross-sectional study carried out in ICU /emergency deptt. of Khyber teaching hospital Peshawar from March 2019 to August 2019. A total of 75 patients including 51 patients having blood culture positive and 24 patients having blood culture negative were selected through non – probability consecutive sampling technique. Results: In our study, mean evels were significantly higher for blood culture positive than for blood culture negative cases (p value 0.000) . Cut off level of serum PCT for identification of bacterial sepsis was 0.5ng/ml in critically ill patients . Plasma PCT levels have sensitivity, specificity, PPV and NPV of 92% , 80% , 90.2% , and 83.3% respectively in determining blood culture positive than blood culture negative patients . Furthermore it was revealed that PCT had an (AUC =0.97) for culture positive cases and had an (AUC= 0.025) for blood culture negative cases. Conclusion: Sensitivity for PCT is greater than specificity , so serum PCT assay is a useful screening test and also a quick indicator of bacterial sepsis in critically ill patients.